2017
DOI: 10.1038/s41598-017-06418-2
|View full text |Cite
|
Sign up to set email alerts
|

The basal free fatty acid concentration in human saliva is related to salivary lipolytic activity

Abstract: Fat perception during eating is a complex sensation that involves various sensory modalities, such as texture, aroma and taste. Taste is supported by the discovery of fatty acid receptors in the tongue papillae. Dietary fat is mainly composed of esterified fatty acids, whereas only free fatty acids can bind to taste receptors. Some authors have mentioned the necessity and efficiency of salivary lipolytic activity to hydrolyse the esterified fatty acids present in foods and enable fat perception. Our hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…This result cannot be compared to the literature due to the lack of data available on age‐related effects on lipolytic activity. A recent work by Neyraud et al () reported a median lipolytic activity value of 0.28 mU/ml for a group of 54 subjects with an average age of 51 years. This result fits in the range of lipolytic activity observed in the present study (0.17–1.1 mU/ml across the different age groups).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This result cannot be compared to the literature due to the lack of data available on age‐related effects on lipolytic activity. A recent work by Neyraud et al () reported a median lipolytic activity value of 0.28 mU/ml for a group of 54 subjects with an average age of 51 years. This result fits in the range of lipolytic activity observed in the present study (0.17–1.1 mU/ml across the different age groups).…”
Section: Discussionmentioning
confidence: 95%
“…Lipase is another enzyme that is speculated to contribute to the oral digestion of foods. Even though lipase has not yet been isolated from human saliva, the relationship between lipolytic activity and perception has been suggested (Neyraud et al, 2017;Neyraud, Palicki, Schwartz, Nicklaus, & Feron, 2012;Poette et al, 2014).…”
Section: Salivary Enzymes Can Partially Explain Variations In Perceptmentioning
confidence: 99%
“…For Neyraud et al (), the levels of free fatty acids were calculated from the percentage of each of the fatty acid related to the total mean.…”
Section: Ionsmentioning
confidence: 99%
“…Both nonesterified and esterified lipids are secreted in human saliva at concentrations of 1-4 μg/L depending on their form (Larsson, Olivecrona, & Ericson, 1996;Neyraud et al, 2017). Lipids also possess sensory properties that are dependent upon their form.…”
Section: Lipidsmentioning
confidence: 99%
“…Lingual lipase in rodents has strong lipolytic activity and plays a critical role in oral detection of fats [56]. Physiological role of salivary lipolytic activity in the regulation of the basal FFA concentration could be involved in fat taste sensitivity [57]. During chewing, saliva helps in preparing the food bolus by agglomerating the formed particles, and it initiates enzymatic food breakdown [58].…”
Section: Role Of Digestionmentioning
confidence: 99%